Factors of Father Support Related to Exclusive Breastfeeding Behavior in Semarang City - Puja Anggun Febiani; Zahroh Shaluhiyah; Sri Achadi Nugraheni (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
A breastfeeding father is a father who takes part in supporting his wife to breastfeed the baby. The success of exclusive breastfeeding can be achieved if there is husband involvement in it. Breastfeeding really requires a stable emotional condition. The husband’s role in the breastfeeding process in Indonesia is still lacking so that the husband has to understand the importance of support for a mother. This study aims to analyze the factors of father support related to exclusive breastfeeding behavior in Semarang City. This study was an analytical study with a Cross-Sectional design using a Simple Random Sampling technique. The data were collected using a questionnaire. The Chi-Square Test was used for bivariate analysis and the logistic regression test for multivariate analysis. The study results showed that variables of knowledge, attitude, emotional support, and instrumental support were related to exclusive breastfeeding in Semarang City. The most dominant factor influencing breastfeeding behavior was instrumental support with an OR value = 52.044. Father awareness regarding the important role of the breastfeeding father in supporting exclusive breastfeeding is expected to be improved. Family and health workers must collaborate to encourage the important role of the breastfeeding father.